Central Tolerance Mechanisms to TSHR in Graves’ Disease: Contributions to Understand the Genetic Association - Pujol-Borrell, Ricardo; Álvarez-Sierra, Daniel; Jaraquemada, Dolores; Marín-Sánchez, Ana; Colobran, Roger (Hormone and Metabolic Research, 2018)
In the last 3 years, the association of thyrotropin receptor gene (TSHR) variations to Graves’ disease (GD) has been confirmed. It is now well established that a 30 Kb region of intron 1 of the TSHR gene is linked to GD predisposition. Elucidating the mechanism(s) by which these polymorphisms confer susceptibility is difficult but would constitute an important advance in endocrine autoimmunity in general. Two hypotheses, both postulating TSHR gene regulatory mechanisms, are discussed. One postulates differential level of expression in the thymus, involving central tolerance. The other postulates a shift in TSHR differential splicing leading to the production of soluble proteins that will have easy access to antigen presenting cells, so it is focused in peripheral tolerance. A combination of the 2 hypothesis is feasible, especially under the light of recent evidence that have identified epigenetic factors acting on TSHR intron 1.
Keywords: TSHR; Graves’ disease; central tolerance; genetics of Graves’ disease; genetic association